Baicalin suppresses autophagy-dependent ferroptosis in early brain injury after subarachnoid hemorrhage. Issue 1 (1st January 2021) - Zheng, Bao; Zhou, Xiwei; Pang, Lujun; Che, Yanjun; Qi, Xin
ABSTRACT: Early brain injury, characterized by massive cell apoptosis or death, is identified as a critical pathophysiological process during subarachnoid hemorrhage (SAH). Ferroptosis, a class of autophagy-dependent cell death discovered in 2012, is induced by iron-dependent lipid peroxidation accumulation. The present study was designed to study the role of baicalin in autophagy-dependent ferroptosis in early brain injury after SAH. Neurological scores and brain water content were measured to evaluate brain injury. Measurement of iron ion, malondialdehyde (MDA), lipid reactive oxygen species was conducted for ferroptosis evaluation. Immunofluorescence staining, western blotting, and flow cytometry analysis were used to evaluate autophagy and apoptosis. First, we observed that, compared with sham rats, SAH rats had lower neurobehavioral scores. Next, baicalin was proven to decrease the Fe 2+, malondialdehyde, and ROS levels in the brain tissues of rats. Also, baicalin was confirmed to suppress the beclin1, LC3-II, and LC3-I protein levels in rat brain tissues. Moreover, we found that baicalin inhibited neuronal apoptosis. Finally, the effects of baicalin on brain injury in the SAH rats were verified. Overall, our results demonstrated that baicalin suppressed autophagy-dependent ferroptosis in EBI after SAH.